DFT Studies of Distinct Anilines with p-Hydroxycinnamic Acids for Antioxidant Profile - Kumar, Ch. Ravi S.; Jha, Anjali; Deepthi, Sri (Medicinal Chemistry, 2021)
Background: Life style and jobs in current situations have generated increased free radicals such as hydroxyl (OH•) and superoxide (O2•) radicals, thereby increasing stress in humans. Interest in search of antioxidants that trap these free radicals has increased to relieve stress. β-carotene (provitamin A), ascorbic acid (vitamin C), tocopherol or vitamin E, Trolox; butyl hydroxy toluene and phenolic compounds are the well-known antioxidants. Several methods evaluate the antioxidant property existing in natural substances (medicinal plants and agri-food products) and synthetic compounds (2-methyl-3- (pyrrolidin-2-ylideneamino) quinazolin-4 (3H) –one and 3,3'- (1,4- phenylenebis (methanylylidene)) bis (azanylylidene) (2-methyl-quinazolin-4 (3H) -one). Objective: The objective of this study is to focus on complexes with p-hydroxycinnamic acids to trap free radicals in a greener way. Methods: Spectroscopic shifts and structural studies were employed to attribute electronic properties responsible for antioxidant profile. Spectroscopic shifts in wavenumbers were attributed with Fourier Transform Infrared Spectra (FTIR) and Fourier Transform Raman spectra (FT Raman Spectra). Structural studies were performed with Gaussian package, electron density method the B3LYP method, basis set 6-31(d) for attributing electronic properties responsible for antioxidant profile. Results: Interpretation of FTIR spectra revealed spectroscopic shifts in wavenumbers in all the complexes responsible for bonding. Further, studies confirmed the formation of complex with reduced intensities in Raman spectra. Computational studies revealed enhancement in molecular and electronic properties responsible for antioxidant power. Conclusion: Studies revealed that complex with p-nitroaniline contribute to greater acceptor and donor power responsible for antioxidant power. These higher powers suggest the best antiradicals to trap free radicals.
Keywords: Antioxidant profile